JURIDICAL STUDY ON THE IMPLEMENTATION OF CONFIGURATION OF PROPERTY OF CRIMINAL OFFENDERS CORRUPTION IN INDONESIA - Utreck Ricardo; Yasmirah Mandasari Saragih; Boniek Juventus; Haposan Silalahi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Current efforts to eradicate corruption are not only focused on arresting and providing criminal sanctions against the perpetrators, but also through efforts to recover financial and economic losses to the state by confiscating assets or property belonging to perpetrators of criminal acts of corruption. Thus, efforts to eradicate criminal acts of corruption are not only follow the suspect, but also follow the money/assets. The objectives of this writing are to: (1) Explain the mechanism for confiscating the assets of perpetrators of criminal acts of corruption. (2) Test whether the confiscation of assets of perpetrators that were not obtained from criminal acts of corruption can also be carried out. This research uses empirical normative juridical research methods. The primary data used is interviews with investigators at the Prosecutor's Office, while the secondary data used is the Law on the Eradication of Corruption Crimes and the Law on Prevention and, the Criminal Procedure Code and the Criminal Code, then the tertiary data is from books and journals. Based on the research results, it can be concluded that the mechanism for confiscating the assets of perpetrators of criminal acts of corruption uses 2 methods, namely: through criminal channels (in personam forfeiture), and through civil channels (in rem forfeiture). Apart from that, confiscation can be carried out on the assets of perpetrators of criminal acts of corruption, even if these assets were not obtained from criminal acts of corruption, as a consequence of the perpetrator's actions who must be held accountable for their actions which have harmed state finances.